Interference between the Oral and the Written in the Historical Novel “The Secret History of Numan Abd al-Hafiz” - Mamdouh Farrag (Şarkiyat Mecmuası)
Novels and history have an intertwined relationship, as both rely on shared elements such as memory and narration to convey events and characters. Many writers such as Ali Ahmed Bakathir, Jurji Zaydan, and Aly Al-Garem have preferred the historical novel as a medium for exploring historical events and characters, focusing on both the form and content in their works. This relates to many reasons such as culture, education, having the glory of Arabia and Islam emerge, and the call to imitate role models. In spite of the importance of these objectives, the representation of history in the narrative blog in recent history has not merely been to retain the past but has also been used to mask the reality and incidents of the present, as has been represented in Gamal al-Ghitani’s novel Al-Zini Barakat and Mohamed Jibril’s From the Papers of Abu Al-Tayyib Al-Mutannabi. This study analyzes Mohamed Mustagab, who blended imagination and history in his narrative writing, and his work The Secret History of Numan Abd al-Hafiz. The study aims to identify the interferences between the novel and history by focusing on the techniques the author employed to blend oral and written traditions while maintaining the literary and imaginary aspects of the text. Additionally, the study explores the author’s use of a language resembling folk narration characterized by distinct linguistic and grammatical features in comparison to formal scientific writing.